2015
DOI: 10.1364/josaa.32.001556
|View full text |Cite
|
Sign up to set email alerts
|

Focus correction in an apodized system with spherical aberration

Abstract: We performed a theoretical and computational analysis of the through-focus axial irradiance in a system with a Gaussian amplitude pupil function and fourth- and sixth-order spherical aberration (SA). Two cases are analyzed: low aberrated systems, and the human eye containing significant levels of SA and a natural apodization produced by the Stiles-Crawford effect. Results show that apodization only produces a refraction change of the plane that maximized the Strehl ratio for eyes containing significant levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…If an optical system measures the refraction of an eye under cycloplegia using minimum RMS refraction, which is equivalent to the system looking for maximum intensity of the image of a point source on the retina, 31 such as many autorefractometers, or similar to the use of retinoscopy, 32 the accommodation or the AA will depend on the image formed by rays passing through the whole pupil. Then, accommodation will be smaller than measurements obtained when only paraxial rays are taken into account (black rays in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If an optical system measures the refraction of an eye under cycloplegia using minimum RMS refraction, which is equivalent to the system looking for maximum intensity of the image of a point source on the retina, 31 such as many autorefractometers, or similar to the use of retinoscopy, 32 the accommodation or the AA will depend on the image formed by rays passing through the whole pupil. Then, accommodation will be smaller than measurements obtained when only paraxial rays are taken into account (black rays in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). As a consequence, subjects could tolerate greater lags in accommodation because the tolerance is larger to negative defocus 31 …”
Section: Discussionmentioning
confidence: 99%
“…The role of the intensity distribution of the input beam has been investigated in the literature [95]. Focus correction in an apodized system with spherical aberration has been investigated by Bernal et al [96]. Recently Naresh et al have shown the effect of a parabolic apodizer on improving the imaging of optical systems with coma and astigmatism aberration [97].…”
Section: Theory Of Tight Focusing For Circular Basis Hyops Beamsmentioning
confidence: 99%
“…It has been used in the form of pinhole contact lenses to improve vision in eyes with markedly irregular corneas [7]. Furthermore, the benefits on vision of the StilesCrawford effects [8][9][10][11][12] can be potentially simulated with an apodized pupil [13,14]. It has also been shown that the natural limitation of the eyelids caused by ptosis may itself modify the refractive state of the eye [10].…”
Section: Introductionmentioning
confidence: 99%